Social construction of market access for family farmers in Brazil - Sabourin, Eric (2018)
The article deals with the social construction of family farmers' markets in northeastern and midwestern Brazil based on an analysis of the articulation and complementarity between modes of collective action and reciprocal relationships. Methodologically, marketing strategies and logics were observed alongside a sample of families involved in different circuits or chains: direct sales, public procurement, and long circuits with intermediaries. The methodology combined the study of collective marketing practices and strategies with the role of reciprocal relationships between families and communities. The results show the importance of organizational processes and public and private support for the implementation of these strategies. The main conclusion is that reciprocal relationships that produce and consolidate social ties are also essential for facilitating access to markets and contributing to the sustainability of families' marketing activities, complementing collective action and public policies.